The Draupner wave: A fresh look and the emerging view. Issue 8 (19th August 2016) - Cavaleri, Luigi; Barbariol, Francesco; Benetazzo, Alvise; Bertotti, Luciana; Bidlot, Jean‐Raymond; Janssen, Peter; Wedi, Nils
Abstract: Using the new high‐resolution operational model of ECMWF, we revisit the storm during which the Draupner freak wave of 1 January 1995 was recorded. The modeling system gives a realistic evolution of the storm highlighting the crucial role played by the southward propagating polar low in creating the extreme wave conditions present at the time the freak wave was recorded. We also discuss the predictability of the meteorological event. The hindcast wave spectra allow a new analysis of the probability of occurrence of the Draupner wave that we analyze not only in time at a specific position, but also in space. This leads us to discuss how exceptional the so‐called freak waves really are. For a given sea state, as characterized by the significant wave height, they are namely part of the reality of the ocean, the key point being the probability of encountering them. In this respect, the often considered record at a specific location can be misleading because the probability of detecting a freak wave must be considered both in space and time. Key Points: High resolution and new model physics identify key characters of the Draupner storm Conditions favorable to freak waves peaked at the time of the Draupner wave Definition of the concept of "dynamical swell"